2012
DOI: 10.1128/aem.00911-12
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vivo Gene Expression of Major Leptospira Proteins in Resistant or Susceptible Animal Models

Abstract: ABSTRACTTranscripts ofLeptospira16S rRNA, FlaB, LigB, LipL21, LipL32, LipL36, LipL41, and OmpL37 were quantified in the blood of susceptible (hamsters) and resistant (mice) animal models of leptospirosis. We first validated adequate reference genes and then evaluated expression patternsin vivocompared toin vitrocultures. LipL32 expression was downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Their results indicated that the lipl32 expression in hamsters was significantly higher than in mice. 20 This result may correlate with the present data in which the responses of hamster LipL32 -specific CD4 + T cells were higher than those of the mouse model. Although the response of hamster CD4 + T cells was dramatically increased in in vitro re-stimulation with rLipL32, lower levels of IFN-γ and IL-4 producing CD4 + T cells were detected.…”
Section: Discussionsupporting
confidence: 82%
“…Their results indicated that the lipl32 expression in hamsters was significantly higher than in mice. 20 This result may correlate with the present data in which the responses of hamster LipL32 -specific CD4 + T cells were higher than those of the mouse model. Although the response of hamster CD4 + T cells was dramatically increased in in vitro re-stimulation with rLipL32, lower levels of IFN-γ and IL-4 producing CD4 + T cells were detected.…”
Section: Discussionsupporting
confidence: 82%
“…Levels of lipL41 transcript (Matsui et al, 2012) and LipL41 protein (Cullen et al, 2002; Nally et al, 2001b) are remarkably unaffected by temperature, osmolarity and other environmental factors. The stability of LipL41 expression is useful as a control when studying the effects of growth conditions on the expression of other genes and proteins.…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…The gene transcript 528 ZENG ET AL. levels were normalized to the level of L. interrogans 16S, as described previously (Matsui et al, 2012).…”
Section: Rna Extraction and Real-time Pcr Detectionmentioning
confidence: 99%